Analysing the State of Inclusive Education in China: Challenges and Perspectives - Zainab Merchant (2025)
The global focus on inclusive education has intensified, with countries working to ensure equal school access for all, including those with disabilities. China has made significant legislative advancements to support inclusive education in line with international standards. However, challenges remain in implementing inclusive practices and delivering quality education to children with special needs. This study analyses China’s inclusive education system, examining its policy framework, social and cultural context, historical evolution, and implementation challenges. It highlights the need for comprehensive reforms to address gaps and foster true inclusion. Key recommendations include ongoing monitoring, clear policy directives, increased family involvement, and enhanced teacher training. The study calls for a holistic approach to ensure social inclusion and equity, aiming to build a more inclusive society for individuals with disabilities in China.